2009
DOI: 10.1063/1.3111782
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic particle transport using the lattice Boltzmann method

Abstract: Peristaltic transport refers to a class of internal fluid flows where the periodic deformation of flexible containing walls elicits a non-negligible fluid motion. It is a mechanism used to transport fluid and immersed solid particles in a tube or chan nel when it is ineffective or impossible to impose a favorable pressure gradient or desirous to avoid contact between the transported mixture and mechanical mov ing parts. Peristaltic transport occurs in many physiological situations and has myriad industrial app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…This recirculation zone will be important for transport and mixing. The identification of this flow structure is not new and fluid trapping (and the trapping of solid particles) inside similar recirculation zones has been observed in other peristaltic flow models that use prescribed wall shape and motions [27]. Inside the region where the walls are contracted we also see a strong jet of retrograde flow which extends just outside the region of the muscular contraction.…”
Section: /37mentioning
confidence: 66%
“…This recirculation zone will be important for transport and mixing. The identification of this flow structure is not new and fluid trapping (and the trapping of solid particles) inside similar recirculation zones has been observed in other peristaltic flow models that use prescribed wall shape and motions [27]. Inside the region where the walls are contracted we also see a strong jet of retrograde flow which extends just outside the region of the muscular contraction.…”
Section: /37mentioning
confidence: 66%
“…This seems to contradict the corresponding results presented here for an axially placed vesicle in an open tube, where we observe very little difference between the transport speeds of tracers and vesicles. However, Connington et al (2009) showed that the increased transport speed observed in Fauci (1992) was due to the periodic copy of the circular particle at every wavelength of the channel. When periodic channels with only one finite-sized particle per five or ten wavelengths were tracked, the transport speed did not increase with particle diameter (Connington et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…However, Connington et al (2009) showed that the increased transport speed observed in Fauci (1992) was due to the periodic copy of the circular particle at every wavelength of the channel. When periodic channels with only one finite-sized particle per five or ten wavelengths were tracked, the transport speed did not increase with particle diameter (Connington et al, 2009). Again, we see the crucial dependence upon boundary conditions imposed at the tube ends.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The LBM has been successfully applied to a wide range of complex transport problems, such as porous flow [7], multiphase flow [13], particle flow [20] and reactive transport processes [21][22][23]. In the LB equation, fluid motion is represented by a set of particle distribution functions.…”
Section: Methodsmentioning
confidence: 99%